Smart Fireball Extinguisher - FZ Trading / Nurfatin Fadhilah Zain Karimy - Zain Karimy, Nurfatin Fadhilah (2020)
FZ Trading is a partnership company that performed a modification on the existing products. We are located at Cyberjaya, Selangor. FZ Trading focus on wholesale business structure, that mean our operation is to produces mass of product and sell to the wholesaler or retailer that will turn around and sell the product at their stores. FZ Trading is a company which is focuses on securities industry in Malaysia. We are producing fire ball extinguisher. The fire ball extinguisher from our company is target to customers all around Malaysia especially household and building area. We create a new product from an existence product which is better and highly efficient and more important zero emission. This means our product is helping people to save their life.